A study of CD4 count and cervical epithelial abnormality in HIV positive women - Varalakshmi KP; R. Sujeeva Swapna; Hariharanada Sarma; Monoranjan Monoranjan; Neeraja M (International Journal of Medical Research and Review, 2016)
Introduction: Cervical epithelial cell abnormalities (ECA) can result in cervical cancer which is the most common cause of cancer related death especially in developing countries. The aim of the present study is to find the association of CD4 count and Cervical epithelial abnormality in HIV positive women.Materials and Methods: A study of association between cervical epithelial abnormality and CD4 count in HIV positive women was taken up in a Care and Support Hospital in collaboration with the Department of Pathology, Government Medical College, Ananthapuramu. Based on the observations, periodic cervical screening in HIV positive women is emphasized.Results: 3.03% of women showed presence of cervical epithelial abnormality among HIV positive women. More number of HSIL (50%) followed by LSIL (28.2%), ASCUS (20.16%) and Carcinoma Cervix (1.6%).Conclusion: Present study also emphasizes that patients with low CD4 count are at high risk of developing precancerous lesions of cervix. Hence periodic biannual cervical screening is required for HIV positive women whose CD4 count is below 200, to bring down the incidence of cervical malignancy and premalignant conditions.